Breast cancer management in middle-resource countries (MRCs): consensus statement from the Breast Health Global Initiative. - Yip, C.; Cazap, E.; Anderson, B.O.; Bright, K.L.; Caleffi, M.; Cardoso, F.; Elzawawy, A.M.; Harford, J.B.; Krygier, G.D.; Masood, S.; Murillo, R.; Muse, I.M.; et al. (2011)
In middle resource countries (MRCs), cancer control programs are becoming a priority as the pattern of disease shifts from infectious diseases to non-communicable diseases such as breast cancer, the most common cancer among women in MRCs. The Middle Resource Scenarios Working Group of the BHGI 2010 Global Summit met to identify common issues and obstacles to breast cancer detection, diagnosis and treatment in MRCs. They concluded that breast cancer early detection programs continue to be important, should include clinical breast examination (CBE) with or without mammography, and should be coupled with active awareness programs. Mammographic screening is usually opportunistic and early detection programs are often hampered by logistical and financial problems, as well as socio-cultural barriers, despite improved public educational efforts. Although multidisciplinary services for treatment are available, geographical and economic limitations to these services can lead to an inequity in health care access. Without adequate health insurance coverage, limited personal finances can be a significant barrier to care for many patients. Despite the improved availability of services (surgery, pathology, radiology and radiotherapy), quality assurance programs remain a challenge. Better access to anticancer drugs is needed to improve outcomes, as are rehabilitation programs for survivors. Focused and sustained government health care financing in MRCs is needed to improve early detection and treatment of breast cancer.